Pembentukan Karakter Religius dan Sikap Peduli Sosial pada Peserta Didik di MA Alkhairaat Sibalaya: The Development of Religious Character and Social Concern among Students at MA Alkhairaat Sibalaya - Nelam Lestari; Sri Dewi Lisnawaty; Ardillah Abu (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
This study aims to explore the implementation of religious character building and social care attitudes among students at MA Alkhairaat Sibalaya. The research employs a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that the development of religious character and social care attitudes is carried out in a structured manner through the stages of planning, implementation, and evaluation. The values instilled include honesty, discipline, and responsibility, which are integrated into worship activities, academic tasks, and social activities within the school environment. Honesty is developed through habitual worship practices, academic evaluations, and social interactions. Discipline is formed through punctual attendance, timely completion of academic assignments, and active participation in social activities. Responsibility is fostered through student involvement in religious activities, academic responsibilities, and participation in social and organizational activities. The impact of this program is evident in the increased student awareness in worship, time discipline, social participation, as well as the growth of empathy and care for others.